Key policy objectives for European agricultural policies: Some reflections on policy coherence and governance issues - Silvia Coderoni (Bio-based and Applied Economics (BAE), 2023)
Food security and environmental sustainability are global challenges that must be addressed together to be solved. After stressing the importance of solving the challenges of producing enough food to feed a growing population while preserving the climate and the environment, this analysis discusses some issues related to the policy coherence (PC) approach that should be followed. Within-policy and between-policies coherence problems are assessed and discussed, and governance problems related to the PC approach are presented. Key points for a likely approach to PC include goal-based governance grounded in the analysis of synergies and trade-offs.
Keywords: Q15; Q18; Q57; Q54; 330; Agricultural Policy; Environmental Sustainability; Food Security; Governance; Policy Coherence